Dynamics and damage analysis of blueberry fruit collisions - Bao, Yudong; Zeng, Jiasai; Liu, Yuying (International Journal of Agricultural and Biological Engineering, 2026)
Fruits are easily damaged by collision during mechanical harvesting of blueberries, affecting quality. In this study, theoretical analysis, numerical simulation, and experimental verification are comprehensively employed to investigate the mechanical behavior and damage mechanism of blueberry fruit collisions. A nonlinear collision dynamics model for fruits is constructed based on Hertzian theory; the collision force is found to be related to the mass, the coefficient of restitution, the material properties of the collided object, and the collision velocity. A discrete element simulation model was created, as was a finite element simulation model. The fruit collision type was determined, and the analysis showed that when the collision velocity of the fruit-rigid plate collision model was increased from 1 m/s to 3 m/s, the peak contact stress increased from 64 000 Pa to 110 000 Pa, the peak collision force increased from 1.85 N to 6.75 N, and the damage volume increased from 152.72 mm3 to 459.42 mm3, which is more likely to trigger compared to the fruit-fruit collision model plastic deformation. Through the collision test it was determined that blueberry fruit can withstand a maximum collision force in the range of 2.00-3.00 N. More than 300 mm of drop height will cause the damage surface ratio to increase dramatically. The results of the study identified the key factors and thresholds affecting damage, providing a theoretical basis for reducing the damage rate of blueberry fruit and also providing a reference for the mechanical harvesting of other berry fruits. Keywords: blueberry, mechanical harvesting, collision mechanics, fruit damage DOI: 10.25165/j.ijabe.20261902.10030 Citation: Bao Y D, Zeng J S, Liu Y Y. Dynamics and damage analysis of blueberry fruit collisions. Int J Agric & Biol Eng, 2026; 19(2): 39–48.